Theoretical calculation of stress for the start of stress induced martensitic phase transformation in the Shape Memory Alloys NiTi - Ferčec, Janko; Rudolf, Rebeka (Anali PAZU, 2022)
The Shape Memory Alloy Nickel – Titanium NiTi is characterized by particular thermo-mechanical behaviour. Namely, the NiTi alloy showed above the temperature where the fully austenitic phase behaviour has superelasticity. Superelastic behaviour is a property of the material and means that the material during the loading at a given stress causes the diffusion-less phase transformation from austenite to martensite. In doing so, a small rise in stress in the material causes changed elongation. The value for the beginning of transformation in the Shape Memory Alloy NiTi is highly dependent on the method of loading. Under tensile and compressive loading, asymmetrical stress occurs.In the present work we showed experimentally determined stress for the start of the transformation at tension loading and the theoretical calculation of the stress to start the transformation for compressive and shear loading.
Keywords: NiTi alloys; shape memory; superelasticity; stress